2014
DOI: 10.12795/spal.2014.i23.04
|View full text |Cite
|
Sign up to set email alerts
|

Confectio Gari Pompeiani. Procedimiento experimental para la elaboración de salsas de pescado romanas

Abstract: Resumen: El presente trabajo hace públicos por primera vez los resultados de un proceso experimental fruto de la colaboración entre las universidades de Cádiz y Sevilla. Dicho proceso, en el que han participado arqueólogos y bioquímicos, se ha realizado en el Departamento de Ingeniería Química de la Facultad de Ciencias de la Universidad de Cádiz y ha consistido en la identificación de la naturaleza concreta y en la reproducción física de la afamada salsa salada de pescado greco-romana denominada garum (liquam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…1b) and pollen from culinary spices (Curtis, 1979;Bernal et al, 2013). These remnants were characterized as the last garum productions before the Vesuvian eruption (Bernal et al, 2013;Carannante, 2010;García et al, 2014;Curtis, 1979) and were found in the solid form, corresponding to allec.…”
Section: Samples Of the Archaeological Remainsmentioning
confidence: 99%
See 3 more Smart Citations
“…1b) and pollen from culinary spices (Curtis, 1979;Bernal et al, 2013). These remnants were characterized as the last garum productions before the Vesuvian eruption (Bernal et al, 2013;Carannante, 2010;García et al, 2014;Curtis, 1979) and were found in the solid form, corresponding to allec.…”
Section: Samples Of the Archaeological Remainsmentioning
confidence: 99%
“…The temperature was fixed at 50 ± 5 °C to maximize the fish protease activity, and the vessels were sealed for a week and maintained in the dark to simulate an amphorae exposed to the sun. Starting on day 8, the mixture was stirred for 5 min/day for 7 more days (García et al, 2014). At these times, fractions of liquamen and allec were separated by filtering through linen, and the allec fraction -allec reference-was collected -5 kg-and kept deep-frozen until analysis.…”
Section: Allec Reference Samplesmentioning
confidence: 99%
See 2 more Smart Citations